Methodological strategies applied in the esnglish languaje teaching - learning process to develop the writing skill in the first - year student of baccalaureate at José Miguel García Moreno anda José María Velasco Ibarra educational units, in the city of El Guabo, during the academic period 2013 - 2014. - Flores Granda, Clara Jacqueline (2015)
This research was conducted in the city of El Guabo province of El Oro, in the Educational Units José Miguel García Moreno and Jose Maria Velasco Ibarra to determine the level of implementation of methodological strategies in the process of teaching and learning English language for developing writing students in first year of high school, djurante academic period 2013-2014: In order to design and conduct a workshop to enhance the skills of English teachers about teaching strategies to develop updated writing.